ANTESEDEN DAN KONSEKUENE-LOYALTY - Prasetya, Adhitya Yoga (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This paper investigates the antecedents and consequences of customerloyalty in an online business-to-consumer (B2C) context. We identifyeight factors (the 8Cs— customization, contact interactivity, care,community, convenience, cultivation, choice, and character) thatpotentially impact e-loyalty. The paper also reveal that e-loyalty hasan impact on two customer-related outcomes: word-of- mouthpromotion and willingness to pay more.